Symbiodinium-Induced Formation of Microbialites: Mechanistic Insights From in Vitro Experiments and the Prospect of Its Occurrence in Nature - Frommlet, Jörg C.; Wangpraseurt, Daniel; Sousa, Maria L.; Guimarães, Bárbara; Medeiros da Silva, Mariana; Kühl, Michael; Serôdio, João (Frontiers in Microbiology, 2018)
Dinoflagellates in the genus Symbiodinium exhibit a variety of life styles, ranging from mutualistic endosymbioses with animal and protist hosts to free-living life styles. In culture, Symbiodinium spp. and naturally associated bacteria are known to form calcifying biofilms that produce so-called ‘symbiolites’, i.e. aragonitic microbialites that incorporate Symbiodinium as endolithic cells. In this study, we investigated how algal growth and the combined physiological activity of these bacterial-algal associations affect the physicochemical macroenvironment in culture and the microenvironment within bacterial-algal biofilms and how these interactions induce the formation of symbiolites. In batch culture, calcification typically commenced when Symbiodinium spp. growth approached stationary phase and when photosynthetic activity and its influence on pH and the carbonate system of the culture medium had already subsided, indicating that symbiolite formation is not simply a function of photosynthetic activity in the bulk medium. Physical disturbance of bacteria-algal biofilms, via repeated detaching and dispersing of the developing biofilm, generally impeded symbiolite formation, suggesting that the structural integrity of biofilms plays an important role in generating conditions conducive to calcification. Microsensor measurements of pH and O2 revealed a biofilm microenvironment characterized by high photosynthetic rates and by dynamic changes in photosynthesis and respiration with light intensity and culture age. Ca2+ microsensor measurements confirmed the significance of the biofilm microenvironment in inducing calcification, as photosynthesis within the biofilm induced calcification without the influence of batch culture medium and under environmentally relevant flow conditions. Furthermore, first quantitative data on calcification from 26 calcifying cultures enabled a first broad comparison of Symbiodinium-induced bacterial-algal calcification with other calcification processes. Our findings support the idea that symbiolite formation is a typical, photosynthesis-induced, bacterial-algal calcification process that is likely to occur under natural conditions.